2006
DOI: 10.1007/s11365-006-7091-x
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating growing ventures from non-growth firms

Abstract: This is the first step of the studies examining which factors differentiate growing from the non-growth firms. Four hypothesis of new firm performance will be tested with logistic regression method. Venture growth, measured by the growth of turnover, will be explained by entrepreneurial characteristics and motivation, and interaction between the firm and environment. The longitudinal study concentrates on the 86 responses, half of these responses (43) were classified as growing and the other half as non-growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 43 publications
2
20
0
Order By: Relevance
“…The importance of demographic characteristics reflects the competencies entrepreneurs required to succeed in business management. This finding is congruent with previous studies (Harada, 2003;Islam et al, 2011;Littunen & Virtanen, 2006;Unger et al, 2009a). For instance, Islam et al (2014) in a study for Bangladesh found that entrepreneurs' demographic factors such as age, gender, and education greatly influenced small-scale business success.…”
Section: Econometric Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The importance of demographic characteristics reflects the competencies entrepreneurs required to succeed in business management. This finding is congruent with previous studies (Harada, 2003;Islam et al, 2011;Littunen & Virtanen, 2006;Unger et al, 2009a). For instance, Islam et al (2014) in a study for Bangladesh found that entrepreneurs' demographic factors such as age, gender, and education greatly influenced small-scale business success.…”
Section: Econometric Resultssupporting
confidence: 91%
“…For instance, Reynolds et al (2001) report that entrepreneurs with older ages from 25 to 45 years have higher entrepreneurial endeavors and hence are most successful than younger counterparts. Similarly, Harada (2003) and Littunen and Virtanen (2006) observe that older firm managers are endowed with rich business experience and might have gone through different phases of business challenges compared with younger entrepreneurs. Prior empirical studies have shown a positive relationship between age and business success (Kristiansen et al, 2003).…”
Section: Entrepreneur Characteristicsmentioning
confidence: 99%
“…Thus, one of our respondents indicated that taking a set of specialized entrepreneurship courses (and more specifically, working on a business plan) during her undergraduate education helped her "to put all the pieces [from previous business courses] together" and this came in very useful in subsequently launching a new venture. Even though entrepreneurship education, training and skills development come up as factors important for venture success, Littunen and Virtanen (2006) note more work needs to be done to understand the exact nature of the relationship between entrepreneurship education and training, especially relating to specific aspects of new venture success (e.g. mobilizing resources, managing the stages of growth, going for an IPO).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of TEA rate in Finland consists of opportunity-driven entrepreneurship (Arenius, Autio and Kovalainen, 2003). According to Littunen and Virtanen (2006) new firms have equal chances for growth independently of their locality. The firm's location was not significant factor in describing the growth of new firms.…”
Section: Hypothesesmentioning
confidence: 99%